The Prevention of Surgical Site Infection in Elective Colon Surgery - Donald E. Fry (Scientifica)
Infections at the surgical site continue to occur in as many as 20% of elective colon resection cases. Methods to reduce these infections are inconsistently applied. Surgical site infection (SSI) is the result of multiple interactive variables including the inoculum of bacteria that contaminate the site, the virulence of the contaminating microbes, and the local environment at the surgical site. These variables that promote infection are potentially offset by the effectiveness of the host defense. Reduction in the inoculum of bacteria is achieved by appropriate surgical site preparation, systemic preventive antibiotics, and use of mechanical bowel preparation in conjunction with the oral antibiotic bowel preparation. Intraoperative reduction of hematoma, necrotic tissue, foreign bodies, and tissue dead space will reduce infections. Enhancement of the host may be achieved by perioperative supplemental oxygenation, maintenance of normothermia, and glycemic control. These methods require additional research to identify optimum application. Uniform application of currently understood methods and continued research into new methods to reduce microbial contamination and enhancement of host responsiveness can lead to better outcomes.